Neg-empatia. Naturalizzare l’empatia tra mercato e linguaggio - Mazzeo, Marco (Bollettino Filosofico, 2022)
The essay offers a critical survey of some of the most important philosophical attempts to naturalize empathy. We will first analyze a position in favor of empathy as a fundamental cognitive and affective structure from an ethical-political point of view (Iacoboni, Baron-Cohen). Then we will look at the arguments against this approach proposed by Paul Bloom. Finally, the essay will attempt to propose a third theoretical way (the “neg-empathy”) to the problem that places the importance of verbal language at the center of the issue and that is able to remind us of the contingent and historical character of the current neoliberal landscape. Keywords: Biology, Empathy, Neg-empathy, Neuromarketing, Verbal Language